Development of Informatics Science Towards Multimedia - Leony Ariesta Wenno; Nicholas Ndahawali; Galih Sava Al Buhari; Devy Tombokan; Mikael Surentu; Marco Takasihaeng (Syntax Corporation Indonesia, 2024)
This research refers to the development of informatics and multimedia which has undergone a significant transformation, influencing various aspects of life, especially in the fields of education, business and communication. Multimedia, which is a combination of various elements such as text, images, audio, animation and video, has become an important means for convey information effectively and interestingly. The development of information technology, especially the Internet, has accelerated the popularity of multimedia. With the internet, access to various forms of multimedia has become easier, allowing users to learn independently and interactively. In the educational context, multimedia is used as an effective teaching tool, both in class and online, thereby improving the quality of learning and motivating students.